The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1590/0104-07072014002250013
|View full text |Cite
|
Sign up to set email alerts
|

Educative practice with nurses, with a view to humanized care for the newborn in the obstetric center

Abstract: This experience report aimed to describe the development of the educational practice undertaken with nurses for the elaboration of a care proposal directed towards newborns in the obstetric center of a public hospital, based in good practices. It describes: strategies, stages of the workshops, consensuses of the care provided to the newborn, and evaluation of the process. The workshops were constituted of: embracement; interacting and raising awareness; planning, validating and defining paths; problematizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Ao desenvolver esta investigação foi possível comprovar que a educação é uma estratégia relevante e deve permear toda a prática assistencial (15) . É através da relação dialógica que a equipe de saúde compartilha suas crenças, valores, conhecimentos e experiências, promovendo uma reflexão crítica da realidade e possibilitando a transformação de suas práticas diárias (16) . O estudo propiciou a compreensão de que o profissional deve ser estimulado a utilizar suas habilidades e seus próprios conhecimentos para encontrar soluções para os problemas vivenciados em sua prática.…”
Section: Discussionunclassified
“…Ao desenvolver esta investigação foi possível comprovar que a educação é uma estratégia relevante e deve permear toda a prática assistencial (15) . É através da relação dialógica que a equipe de saúde compartilha suas crenças, valores, conhecimentos e experiências, promovendo uma reflexão crítica da realidade e possibilitando a transformação de suas práticas diárias (16) . O estudo propiciou a compreensão de que o profissional deve ser estimulado a utilizar suas habilidades e seus próprios conhecimentos para encontrar soluções para os problemas vivenciados em sua prática.…”
Section: Discussionunclassified
“…This review concluded that the responses are associated with the gestational age and are fundamentally changes in the heart rate and oxygen saturation, facial expressions, such as frowning, squeezing the eyes shut and marking the nasolabial sulcus, crying, among other signs ( 8 ) . The mother experiences a high level of anxiety, stress related to the new role, emotional sensitivity and depressive symptoms ( 9 - 10 ) . Behavioral adjustments are characterized by a lack of maternal skills, which increases when it is first-time mother or when the delivery is performed through a cesarean section ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…To that end, they need to combine practice and theory, in that theory is making, and practice is reflection and action (14) . Therefore, the educational process must be a continuing exercise oriented toward production and development of autonomy, involving decisions and responsibilities for better living (15) . Thus, the supervised curricular internships experienced by students are considered essential, taking into account that work processes during internships allow the acquisition of an identity through performance, to the extent that it flows naturally.…”
Section: Discussionmentioning
confidence: 99%